How to cook everything : the basics : all you need to make great food with 1,000 photos - Bittman, Mark (Hoboken, New Jersey : John Wiley, 2012)
"A 4-color book with more than 1,000 how-to and finished recipe photos"-- Provided by publisher
"The next best thing to having Mark Bittman in the kitchen with youMark Bittman's highly acclaimed, bestselling book How to Cook Everything is an indispensable guide for any modern cook. With How to Cook Everything The Basics he reveals how truly easy it is to learn fundamental techniques and recipes. From dicing vegetables and roasting meat, to cooking building-block meals that include salads, soups, poultry, meats, fish, sides, and desserts, Bittman explains what every home cook, particularly novices, should know.More than 1,000 beautiful and instructive photographs throughout the book reveal key preparation details that make every dish inviting and accessible. With clear and straightforward directions, Bittman's practical tips and variation ideas, and visual cues that accompany each of the 171 recipes, cooking with The Basics is like having Bittman in the kitchen with you. This is the essential how-to cookbook, with more than 1,000 beautiful and helpful photos of step-by-step techniques and finished recipes Special "Basics" pages cover essentials like equipping a kitchen and stocking a pantry, what to look for when buying produce, how to tell when food is done, and more Tips and variations let home cooks hone their skills and be creative How to Cook Everything The Basics is an absolutely essential beginner's cookbook and an irresistible and invaluable guide for accomplished cooks"-- Provided by publisher.
1. Why cook? -- 2. Getting started -- 3. Breakfast -- 4. Appetizers and snacks -- 5. Salads -- 6. Soups and stews -- 7. Pasta and grains -- 8. Vegetables and beans -- 9. Meat -- 10. Poultry -- 11. Seafood -- 12. Breads -- 13. Desserts
Inckudes index
Keywords: Cookbooks; Cooking